The city in late antiquity - Rich, John, 1944- (Leicester-Nottingham studies in ancient society, 1992)
Examines the changes undergone by Roman cities in the Late Roman empire and seeks to explain why urban life disappeared in some regions, while elsewhere cities survived through to the Middle Ages and beyond.